Technical Assistance for the Design of the Nurul Ibad Mertak Wire Mosque, Barabali Village, Batukliang District, Central Lombok Regency - Syakirin, Syakirin; Fahmi, Muhammad Arifudin; Sahwan, Sahwan; Edelweis, Edelweis; Hambali, Ahmad Haidir; Aminullah, Wahyu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
lecturers from the Faculty of Engineering at Universitas Islam Al-Azhar to assist in the renovation design of Masjid Nurul Ibad Mertak Wire, located in Barabali Village, Batukliang District, Central Lombok Regency. The mosque, which has stood since 1998, has deteriorated over time, and the mosque management aims to renovate it. The main challenges faced include the absence of a Detail Engineering Design (DED) and a Budget Plan (RAB), limited funds, and the aging condition of the building. Based on field analysis and interviews with the mosque management, it was found that a new construction is necessary to create a more comfortable and aesthetically pleasing mosque environment. To address this issue, the UNIZAR PKM Team collaborates with the Nurul Ibad Mosque Management to develop the Detail Engineering Design (DED) and the Budget Plan (RAB). The implementation method of this PKM activity consists of preparation, process, and output stages. The preparation stage includes activity planning, cost estimation, and identifying partners following LPPM UNIZAR requirements. Once a partner is found, the team of lecturers and students establishes cooperation with the Nurul Ibad Mosque Management to carry out the PKM activities. The process involves submitting a proposal to LPPM UNIZAR, preparing the necessary PKM documentation, and mobilizing architectural and structural experts. Upon completion, the team leader compiles a community service report to be submitted to LPPM UNIZAR and reports the implementation of the activities to the Nurul Ibad Mosque Management as part of the UNIZAR lecturers' Tridarma.